Technical Factors Affecting to Production of Dried Roasted Pumpkin (Cucurbita) Seed - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Pumpkin seeds are covered by a white husk. Pumpkin seeds are subtly sweet and nutty with a malleable, chewy texture. The seeds of pumpkin are rich in oil and nutrients. Pumpkin seed has been considered as beneficial to health because it contains various biologically active components. It lowers cholesterol level in blood. Drying and roasting are the most important processes giving neccessary alterations to the product. Roasting can enhance flavour through caramelization on the surface of the food. There was no any research mentioned to varify the change of antioxidant (tocopherol) during infrared drying as well as storage. So the objective of the present study was to identify the effect of temperature in infrared drying, roasting condition, packaging and storage to antioxidant (tocopherol) in the dried Pumpkin (Cucurbita) seed. Results demonstrated that drying temperature (42 oC), roasting (155 oC in 4 min), vaccum packing in polyethylen (PA) bag and keeping in 4 oC were recommended to maintain the tocopherol, total phenolic and antioxidant activity in the final products for 12 weeks. The effect of drying, roasting temperature and time were clearly demonstrated to produced dried roasted pumpkin seed.Keywords: Pumpkin, Drying, Roasting, ANTIOXIDANT, tocopherol, Vaccum.